A new Brazilian species of Myrcia (Myrtaceae) and a new synonym for Psidium amplexicaule - Santos, Leidiana Lima; Sales, Margareth Ferreira; Sobral, Marcos (Phytotaxa, 2016)
Myrcia arenaria, a new species of Myrcia sensu lato, is described, illustrated and compared with related species. The species is recognized by a combination of characters, which include elliptic to oval foliar blades, flower buds tearing at anthesis into 3 irregular lobes or 5 regular lobes; lobes obovate, apiculate, sericeous at the base and flowers without petals. This taxon seems to be restricted to the coastal areas of northeastern Brazil, growing in the restingas located in the states of Alagoas, Bahia, Pernambuco, and Sergipe. Additionally, we also proposed the synonymization of Marlierea leal-costae with Psidium amplexicaule. We also present a map showing the geographical distribution of the species.